Is Blood Pressure Lowering in the Very Elderly With Previous Stroke Associated With a Higher Risk of Adverse Events? - Damien Tharmaratnam; Christopher C. Karayiannis; Taya A. Collyer; Hisatomi Arima; Leslie A. McClure; John Chalmers; Craig S. Anderson; Oscar R. Benavente; Carole L. White; Ale Algra; Chris Moran; Thanh G. Phan; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background We investigated whether blood pressure lowering for secondary prevention is associated with a reduction in recurrent stroke risk and/or a higher risk of adverse events in very elderly compared with younger trial participants. Methods and Results This is a random effects meta‐analysis of randomized controlled trials of blood pressure lowering for secondary stroke prevention to evaluate age‐stratified (<80, ≥80 years) risk of adverse events. Ovid‐MEDLINE was searched for trials between 1970 and 2020. Summary‐level data were acquired including outcomes of stroke, cardiovascular events, mortality, and adverse events. Seven trials were included comprising 38 596 participants, of whom 2336 (6.1%) were aged ≥80 years. There was an overall reduction in stroke risk in the intervention group compared with controls (risk ratio [RR], 0.90 [95% CI, 0.80, 0.98], I2=49%), and the magnitude of risk reduction did not differ by age subgroup (<80, ≥80 years). There was no increase in the risk of hypotensive symptoms in the intervention group for patients aged <80 years (RR, 1.19 [95% CI, 0.99], 1.44, I2=0%), but there was an increased risk in those ≥80 years (RR, 2.17 [95% CI, 1.22], 3.86, I2=0%). No increase was observed in the risk of falls, syncope, study withdrawal, or falls in either age subgroup. Conclusions Very elderly people in secondary prevention trials of blood pressure lowering have an increased risk of hypotensive symptoms, but with no statistical increase in the risk of falls, syncope, or mortality. However, evidence is lacking for frail elderly with multiple comorbidities who may be more vulnerable to adverse effects of blood pressure lowering.